The effect of combination of constraint induced movement therapy with bimanual intensive therapy on upper limb function of children with hemiplegic cerebral palsy - Hajar Sbaour Eghbali Mostafakhan; Mehdi Rassafiani; Seyed Ali Hosseini; Nazila Akbarfahimi; Masuod Karimloo (Vesnu Publications, 2013)
Introduction: Constraint- Induced Movement Therapy (CIMT) and bimanual approach (BIM training) are a promising treatment for upper limb function improvement in children with spastic hemiplegia. CIMT involved restraint of non-involved upper extremity and intensive practice with involved upper extremity. BIM training is complementary to other treatments of upper extremity and improves bimanual coordination using structured task practice embedded in bimanual play and functional activities. This study was aimed to evaluate the influence of combination of CIMT with BIM training on fine motor skills of children with hemiplegic cerebral palsy. Materials and Methods: In this study, twenty five children with hemiplegic cerebral palsy aged 5-10 years participated and randomly assigned into two intervention and control groups. Children in Control group received current occupational therapy intervention. Subjects in intervention group received a combination of CIMT and BIM training in addition to current occupational therapy. Each session was started with restraint on non-involved upper extremity and practicing with involved upper extremity for three hours. This was followed with BIM training for another three hours. This process lasted for 10 out of 12 consecutive days. Upper limb function and muscle tone were assessed by Jebsen-Taylor test of hand function and modified Ashwort scale, respectively. Results: Upper limb function in intervention group significantly improved (P < 0.05) compared with control group, however the level of spasticity was not significantly different between two groups (P > 0.05). Conclusion: Our findings suggest that combination of constraint induced movement therapy and bimanual intensive therapy improved upper limb Function in the hemiplegic cerebral palsy children. Keywords: Upper extremity function, Constraint induced movement therapy, Bimanual training, Hemiplegia